2005
DOI: 10.1248/bpb.28.2162
|View full text |Cite
|
Sign up to set email alerts
|

Bofutsushosan, a Traditional Chinese Formulation, Prevents Intimal Thickening and Vascular Smooth Muscle Cell Proliferation Induced by Balloon Endothelial Denudation in Rats

Abstract: Bofutsushosan (BOF), a traditional Chinese formulation (Kampo formulation inThis model has a similar pathologic process to atherosclerosis and is considered to be an "accelerated atherosclerosis" model. BOF extract also dose dependently inhibited the migration of cultured VSMCs. BOF extract suppressed serum lipid levels, which are a major risk factor for atherosclerosis. These findings clarified the usefulness of BOF in cardiovascular risk-reduction therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In addition, the R 2 level in the multivariate analysis was relatively low (R 2 ¼ 0.185) ( Table 5) and the mechanism of the beneficial effect of BOF on ambulatory BP variability remains to be determined. Since the improvement in short-term BP variability conferred by BOF add-on therapy on short-term BP is independent of its anti-obesity effect and BP reduction, other factors such as its putative effects on vasoactive substance, endothelial function and/or renal sodium handling would be possible candidates involved [48,49]. We indeed reported that the BOF-mediated improvement in adipose tissue function by amelioration of adipokine dysregulation as well as the reduction of food intake by the appetite-inhibitory property of BOF through suppression on the ghrelin system contribute to the BP lowering effect and favorable metabolic modulation by BOF in a mouse model of human metabolic disorders with obesity [7].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the R 2 level in the multivariate analysis was relatively low (R 2 ¼ 0.185) ( Table 5) and the mechanism of the beneficial effect of BOF on ambulatory BP variability remains to be determined. Since the improvement in short-term BP variability conferred by BOF add-on therapy on short-term BP is independent of its anti-obesity effect and BP reduction, other factors such as its putative effects on vasoactive substance, endothelial function and/or renal sodium handling would be possible candidates involved [48,49]. We indeed reported that the BOF-mediated improvement in adipose tissue function by amelioration of adipokine dysregulation as well as the reduction of food intake by the appetite-inhibitory property of BOF through suppression on the ghrelin system contribute to the BP lowering effect and favorable metabolic modulation by BOF in a mouse model of human metabolic disorders with obesity [7].…”
Section: Discussionmentioning
confidence: 99%
“…Bofutsushosan (BOF), typical Chinese medicine, has been reported to improve atherosclerosis [3], obesity [4][5][6], hypertension, hyperglycemia [6], fatty liver [7,8] visceral fat and insulin resistance [9] in both clinical practice and animal examinations [5]. BOF has the potential to prevent adipogenesis in rat white adipocytes via modulation of gene expression levels [10].…”
Section: Introductionmentioning
confidence: 99%
“…BTS has been reported to inhibit atherosclerosis, 9) obesity, 10) hypertension 11) and hyperglycemia. 12) However, Three Kampo medicines, Boiogito (BOT), Bofutsushosan (BTS) and Orengedokuto (OGT), used for obese patients were investigated for their effects on adipogenesis in cultured rat white adipocytes.…”
Section: )mentioning
confidence: 99%
“…BTS has been reported to inhibit atherosclerosis, 9) obesity, 10) hypertension 11) and hyperglycemia. 12) However, pharmacological evidence for the anti-obesity effects of OGT and BOT remains obscure.…”
mentioning
confidence: 99%